A brief reflection on the process of imprisonment in prison - Faceira , Lobelia da Silva; Silva , Dara de Souza; Azevedo , Thais; Cardoso , Rafaela (Seven Editora, 2023)
The article aims to analyze the prison as an institution within the scope of capitalist society, which produces the annulment of social subjects and the standardization of behaviors and social relations. From a critical analysis of contemporary society and homogenizing social practices affected total institutions, the process of imprisonment that is produced and reproduced in the prison environment will be analyzed. The discussions and the process of construction of the article were produced in the research group "Violence, Prison and Public Policies" and in the research entitled "Social Policies and Prison: an evaluation of the penal execution policy", linked to the Graduate Program in Social Memory (PPGMS) of the Federal University of the State of Rio de Janeiro (UNIRIO). The article based on the theoretical-methodological framework of historical and dialectical materialism problematizes the prison as an environment that sickens the subjects, showing how much the processes of imprisonment modify the identity of the subjects who are inserted in the prison system. DOI:https://doi.org/10.56238/alookdevelopv1-126